2006
DOI: 10.1111/j.1530-0277.2006.00172.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Suppresses LPS‐induced Toll‐like Receptor 4 Clustering, Reorganization of the Actin Cytoskeleton, and Associated TNF‐α Production

Abstract: These data confirm our previous observations, suggest a novel mechanism of EtOH action that involves interference with receptor clustering, and indicate a potential role of actin filaments in the formation of receptor patches, subsequent activation of macrophages by LPS, and production of TNF-alpha.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 51 publications
7
48
0
Order By: Relevance
“…This is associated with decreased production of TNF-␣, and agents that inhibit lipid raft function and rearrangement of the actin cytoskeleton similarly inhibited TNF-␣ production, suggesting that lipid raft-mediated events and rearrangement of the actin cytoskeleton are required for optimum signaling and TNF-␣ expression. In a subsequent study, this relationship was confirmed, and the involvement of TLR4 and CD14 colocalization and clustering were also implicated in activation of macrophages for TNF-␣ production (27). Confocal microscopy revealed that TLR4 and CD14 colocalization and clustering occurred rapidly (3 min) and persisted for at least 1 h. Inhibiting this clustering with cholesterol sequestering agents also inhibited TNF-␣ production.…”
Section: Recent Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…This is associated with decreased production of TNF-␣, and agents that inhibit lipid raft function and rearrangement of the actin cytoskeleton similarly inhibited TNF-␣ production, suggesting that lipid raft-mediated events and rearrangement of the actin cytoskeleton are required for optimum signaling and TNF-␣ expression. In a subsequent study, this relationship was confirmed, and the involvement of TLR4 and CD14 colocalization and clustering were also implicated in activation of macrophages for TNF-␣ production (27). Confocal microscopy revealed that TLR4 and CD14 colocalization and clustering occurred rapidly (3 min) and persisted for at least 1 h. Inhibiting this clustering with cholesterol sequestering agents also inhibited TNF-␣ production.…”
Section: Recent Resultsmentioning
confidence: 66%
“…This led both of us to evaluate the possibility that EtOH acted at the earliest points in signal transduction, possibly by altering lipid rafts. We recently described results indicating that acute EtOH exposure alters LPS-induced redistribution of TLR4 receptor components to lipid rafts, that LPS-induced TLR4 signaling is dependent on normal raft structure, that EtOH also alters the reorganization of the actin cytoskeleton (which is required for full cellular activation by LPS), that EtOH decreases TLR4 and CD14 clustering and colocalization, and that these changes are associated with decreased production of TNF-␣ a key proinflammatory cytokine (27,28). Results were similar for a mouse macrophage like cell line, mouse peritoneal macrophages, and human monocytes.…”
Section: Recent Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TLR4, in particular, has been implicated in Gram-negative LPS signaling, innate immunity and inflammation (Miyake, 2004). Published in vivo and in vitro studies suggest that EtOH suppresses cytokine responses through TLR signaling (Dai and Pruett, 2006;Oak et al, 2006]. In rodent lung, acute EtOH intoxication has also been reported to dampen LPS-induced lung inflammation by impairing TNF-α, MIP-2 and CINC secretion [Boe et al, 2003;D'Souza et al, 1989;Nelson et al, 1989;Zhang et al, 2002].…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of human peripheral blood monocytes with LPS causes clustering of the signaling receptor TLR4 with its accessory protein CD14 [84], and association of this receptor cluster with lipid rafts is thought to be necessary for LPSinduced signal transduction [85]. An increase in membrane fluidity due to ethanol at a concentration of higher than 50 mM inhibits the association of TLR4 with lipid rafts, suppressing LPS-induced TNF- production in mouse macrophage cells [86]. However, it is interesting to note that treatment with MCD does not affect LPS-induced gene expression relating to inflammation [87].…”
Section: Lipid-raft-dependent Uptake Of Particlesmentioning
confidence: 99%